HPLC-PDA and UPLC-ESI-TqD-MS/MS chromatographic analyses of commercial samples of Camellia sinensis (L.) Kuntze (“green tea”) - Silva, J. Z.; Tangerina, M. M.P. [UNESP]; Rocha, C. Q. [UNESP]; Amaral, F. P.; Bento, C. C.; Tahira, L. S. [UNESP]; Vilegas, W. [UNESP]; Sannomiya, M. (My University, 2016)
The analysis by HPLC-PDA, PCA and the injection of standard compounds contributed considerably for the evaluation of the secondary metabolites of four commercial samples of Camellia sinensis. All analyzed samples, except sample number 2, when extracted with ethanol-water mixture, presented catechin derivatives, fenolic acids, methylxanthines and flavonoids, which are commonly found in the species under study. It is possible that sample number 2 does not correspond to C. sinensis or may have been collected in a specific time when the main metabolites were not being produced. Quantification by UPLC-ESI-TqD-MS/ MS of the caffeine content the samples of C. sinensis showed that the values obtained in this work vary between 2.72 to 7.02 g/100 g of crude extract. Moreover, all samples analyzed showed a higher content of caffeine than those previously reported in the literature, except sample number 1. Analysis by PCA of the total ions of the samples showed that sample number 3 infusion is quite different from the other samples. These data allow us to infer that caffeine can be a taxonomic marker in the samples of C. sinensis. However, its presence cannot be conclusive in the quality control of a medicinal plant, since the total composition of caffeine may vary significantly and, therefore, and its consumption may not provide the expected efficacy.
Análises cromatográficas por HPLC-PDA e UPLC–ESI-TqD-MS/MS de amostras comerciais de Camellia sinensis (L.) Kuntze (“chá verde”)
Keywords: Camellia sinensis; HPLC-PDA; TLC; UPLC-ESI-TqD-MS/MS